Improving EFL Students’ Writing Skills Through News Video-Based Learning Strategy In News Item Text - Alyah, Alijawati; Muhayyang, Maemuna; Halim, Abdul (Mutiara: Multidiciplinary Scientifict Journal, 2024)
The present research aimed to discover improvements in EFL students’ writing skills ability through a news video-based learning strategy in news item text. The researcher applied a quantitative method with a one-group pretest-posttest classroom research design (pre-experimental). The data obtained in this research were calculated using the manual statistical method and SPSS statistics version 27. The data were analyzed using the statistical formula of paired sample t-test computation. The population of the research was all of the students in the Acceleration class of MAN 2 Kota Makassar, where the participants consisted of 14 students as well as the sample of the research. Based on the mean score of the students’ pretest was 78 in average to good categories while the mean score of the students’ posttest was 84 in good to excellent categories. Moreover, the result of the data was supported by the t-test analysis, in which the t-test value was higher than the t-table value (-3,113>2,160). So, it can be summarized that H0 was rejected and Ha was accepted, which means a News Video–based Learning Strategy through YouTube of VOA Learning English effectively increases EFL students’ writing skills while composing a news item text paragraph.